Factors influencing delayed treatment among smear positive pulmonary tuberculosis patients - Abdullah, Noor Hashimah (2006)
INTRODUCTION TB remains a great challenge to public health in Malaysia and worldwide. Delay in treatment commencement can result in significant increase morbidity, mortality and transmission. Hence this study is aimed to determine the prevalence of various delays (patient, health service, diagnosis, initiation and total delay) and to identify the factors influencing the patient delay and health service delay. METHOD A crossectional study was done from October 2004 to June 2005 among 178 smear positive pulmonary TB patients in four districts in Kelantan (Kota Bharu, Tumpat, Bachok and Pasir Mas). All patients who fulfilled the inclusion and exclusion criteria and gave consent were recruited due to limited number of patients. Interviewer guided questionnaire was administered and medical record was reviewed to gather patient's information. RESULT The median and inter-quartile range of patient delay, health service delay, diagnosis delay, initiation delay and total treatment delay in days were 30.0(76.00), 7.0(14.50), 3.0(4.00), 3.0(4.00) and 64.0(90.25) respectively. Furthermore, the prevalence and 95%CI of unacceptable delays; patient delay, health service delay, diagnosis delay, initiation delay and total treatment delay were 46.6%(39.3, 53.3), 45.5%(38.2, 52.8), 48.3%(41.0,55.6), 37.6%(30.5,44.8), 61.8% (54.7,68.9) respectively. In multiple logistic regression analysis, the significant factors associated with unacceptable patient delay were age (OR: 3.88;95%CI: 1.35, 11.18; p= 0.0 12), distance from home to first health facilities attended (OR: 3.98; 95%CI: 1.56, 1 0.15; p= 0.004), attending the T/CM practitioners (OR: 10.51; 95%CI, 1.80, 55.39; p=0.006), attending the private practitioners (OR: 0.24, 95%CI: 0.09, 0.60; p= 0.002) and stigma (OR: 4.81; 95%CI: 1.59, 14.60; p=0.006). On the other hand, the significant factors associated with unacceptable health service delay were negative results of initial sputum smear (OR: 14.48; 95%CI: 2.30, 91.34; p=0.004), number of visits to health facilities (OR: 4.99 95%CI: 2.76, 9.03; p= <0.001) and types of first health care facilities attended (OR: 5. 78; 95%CI: 1.58, 21.11; p= 0.008) CONCLUSION This study showed that there was a substantial delay in case finding in Kelantan. Raising public awareness about symptoms of TB, curability and benefit of utilizing available governmental health facilities through health education campaign might shorten the patient delay. Health care personnel in both private and government sectors should be reminded on the important of early diagnosis and prompt treatment of TB. Traditional and complementary practitioners should be well-cooperated in contributing to Malaysian health care system by interacting with both private and governmental health sectors.